Global Perspectives on Recognising Non-formal and Informal Learning: Why Recognition Matters - Singh, Madhu (Technical and Vocational Education and Training: Issues, Concerns and Prospects, 2015)
Professional & Vocational Education; Lifelong Learning/Adult Education; Educational Policy and Politics; Assessment, Testing and Evaluation